Profiling of entrepreneurs and SMEs: issues & challenges - Maulan, Suharni; Ismail, Yusof; Djayusman, Royyan Ramdani; Faradisi, Roghibah Jadwa; Santoso, Bedjo (UMY Press, 2020)
As Malaysia aims to become a high-income country by the year 2020, where the small medium enterprises (SMEs) play critical roles, this chapter focuses on profiling the SMEs and the challenges that they are currently fac-ing. This finding confirms that the majority of Malaysian SMEs is of micro and small size where the issues of financial accessibility and sufficiency are still prevailing. Using factor analysis, 344 data was analyzed, and it was found that the challenges faced by Malaysian SMEs can be divided into four factors, namely: “human resource management (HRM) challenges”, “external chal-lenges”, “entrepreneur competency challenges” and “organizational-related challenges”. It is hoped that these findings will assist the government to identify relevant policies to further enhance the performance of SMEs in Malaysia.